1988
DOI: 10.1002/food.19880320626
|View full text |Cite
|
Sign up to set email alerts
|

Review article Flatulence — Causes, relation to diet and remedies

Abstract: In addition to causing embarrassment and unease, flatulence is linked to a variety of symptoms, some of which may be distressing. This review describes the origins of intestinal gas, its composition and methods which have been developed for its analysis. Emphasis is placed upon the effects of legumes in the diet in producing excessive intestinal gas and, particularly, on the role of raffinose-type oligosaccharides, containing alpha-galactosidic groupings. Suggestions for overcoming the problem are presented, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(68 citation statements)
references
References 101 publications
1
64
1
1
Order By: Relevance
“…Owing to the absence of an a-1,6-galactosidase enzyme capable of hydrolysing the a-1,6-galactosidic linkage, these oligosaccharides accumulate in the lower intestine and undergo anaerobic fermentation by bacteria, which may result in the production of¯atus gases (H 2 , CO 2 and small amounts of CH 4 ), abdominal rumbling, diarrhoea and attendant discomfort. 8,14,15 Therefore, to utilise legumes as more acceptable sources of inexpensive proteins, it is desirable to reduce the¯atulence-inducing agents. Many studies have been conducted to determine the oligosaccharide content of various conventional legumes.…”
Section: ±10mentioning
confidence: 99%
“…Owing to the absence of an a-1,6-galactosidase enzyme capable of hydrolysing the a-1,6-galactosidic linkage, these oligosaccharides accumulate in the lower intestine and undergo anaerobic fermentation by bacteria, which may result in the production of¯atus gases (H 2 , CO 2 and small amounts of CH 4 ), abdominal rumbling, diarrhoea and attendant discomfort. 8,14,15 Therefore, to utilise legumes as more acceptable sources of inexpensive proteins, it is desirable to reduce the¯atulence-inducing agents. Many studies have been conducted to determine the oligosaccharide content of various conventional legumes.…”
Section: ±10mentioning
confidence: 99%
“…Research has shown that, in common with other grain legumes, lentils contain a number of components called antinutritional factors which limit the wider use of harvested crop (1,2). Germination appears to be an inexpensive and effective method of achieving desirable changes in nutritious crops, and germinated seeds have become a widely accepted food item.…”
Section: Introductionmentioning
confidence: 99%
“…Other than small amounts of maltose (Table 1), reducing sugars are in low concentrations, or not detected, in mature dry seeds. Stachyose and other RFO are not digested by humans, chickens, pigs, and other non-ruminant animals but are microbially fermented in the lower gut resulting in flatulence and reduced feed efficiency (Gitzelmann & Auricchio, 1965;Rutloff et al, 1967;Price et al, 1988;Sebastian et al, 2000).…”
Section: Soluble Carbohydrate Composition Of Mature Seedsmentioning
confidence: 99%